1999
DOI: 10.1063/1.480080
|View full text |Cite
|
Sign up to set email alerts
|

Bro/nsted acid sites in gmelinite

Abstract: The structural properties of purely siliceous and Al-substituted protonated gmelinite, a zeolite with a medium-sized unit cell, are investigated by means of first-principles local-density functional calculations. For acid sites introduced into an Al-free structure, optimized geometries are compared with experimental data. The substitution of a Si–O fragment by Al–O–H induces a pronounced local deformation of the structure. Four symmetrically distinct O sites (O1–O4) are classified, according to the pattern of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
12
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 57 publications
4
12
0
Order By: Relevance
“…Simulations are performed with the experimental unit cell determined on hydrated Na-form of gmelinite. 19 As pointed out in our previous work, 21 no significant change of the cell shape is observed with the relaxation of the shape of the zeolite. A dehydration of the zeolite always causes a shrinking of the unit cell.…”
Section: Structural Modelmentioning
confidence: 68%
“…Simulations are performed with the experimental unit cell determined on hydrated Na-form of gmelinite. 19 As pointed out in our previous work, 21 no significant change of the cell shape is observed with the relaxation of the shape of the zeolite. A dehydration of the zeolite always causes a shrinking of the unit cell.…”
Section: Structural Modelmentioning
confidence: 68%
“…A correlation between the T−O−T angle and the protonation energy has been established. It was concluded that sites with larger T−O−T angles are more tolerant to lattice distortions due to replacement of lattice Si with Al giving rise a lower O−H frequency and higher Brønsted acidity and reactivity . On the other hand, a more recent computational study by Jones and Iglesia analyzed the ensemble‐averaged deprotonation energies of six zeolites including MFI (silicalite‐1), BEA (beta), FER (ferrierite), MOR (mordenite), CHA (chabazite) and FAU (faujasite) and concluded that no systematic correlations could be established between the Brønsted acidity and the length of O−H bonds and the Si−O−Al bond angles in those zeolites …”
Section: Brønsted Acidity Of Zeolitesmentioning
confidence: 99%
“…Ab-initio calculations of the OH stretching frequencies [25][26][27] show that this assignment is somewhat simplistic: although on average the hydroxyl stretching frequencies are slightly lower for BAS in the side pocket than in the main channel, the OH modes of both species show broad distributions whose widths are larger than the difference in the averages. Besides their position within the framework, there are other factors contributing to the inhomogeneity of BAS: Sierka et al [5] have emphasized the influence of the overall and local Al concentration, Benco et al [23] have demonstrated that attractive interactions between the hydroxyl group and other framework oxygens over comparatively long distances (~3 Å ) can lead to a pronounced softening of the OHmode.…”
Section: Brønsted Acid Sitesmentioning
confidence: 98%
“…To date, structural optimizations have been performed for a large number of zeolites, ranging from small (chabazite [22]) over medium-sized (gmelinite [23], ZSM22 [24]) to large unit cells (mordenite [25]). The important result is not so much that calculations based on the GGA predict the structural parameters with good accuracy, but the ability to analyze the structure and reactivity of the active sites in proton-exchanged and metal-activated zeolites.…”
Section: Structure Of Framework and Active Sitesmentioning
confidence: 99%